Esophageal leiomyoma and simultaneous overlying squamous cell carcinoma: a case report and review of the literature - Saadat Mehrabi; Mohammad Javad Yavari Barhaghtalab; Safoora Hejazinia; Hossein Saedi (BMC Surgery, 2021)
Abstract Background Squamous cell carcinoma is the most common epithelial tumor of the esophagus. Upper endoscopy with multiple minimally invasive biopsies should be performed to confirm the diagnosis. Leiomyoma of esophagus is rare, but it’s the most common benign submucosal mesenchymal tumor of the esophagus. The simultaneous occurrence of an overlying epithelial lesion and a mesenchymal lesion is very rare. This study aims to show a case operated due to squamous cell carcinoma of esophagus that was postoperatively diagnosed with coexistent esophageal leiomyoma and give a clear overview of the existing literature on it. Case presentation The patient was a 41-year-old woman who underwent three field esophagectomy (McKeown). Pathological evaluation was done, and the patient had poorly differentiated squamous cell carcinoma and multiple leiomyomas. A leiomyoma was found with an invading overlying squamous cell carcinoma. Conclusion It is concluded that esophageal carcinomas may coexist with leiomyomas; preexisting benign tumors may have played an important role in the development of the carcinoma by inducing constant stimulation of the overlying mucosa; endoscopic ultrasonography is recommended to avoid overestimating the extent of tumor invasion and the resultant aggressive radical surgery. As the developing countries had limited equipment, esophageal resection could be the modality of choice in the treatment.